APLIKASI AYO WISATA KE CILACAP DALAM BAHASA MANDARIN DI DINAS PEMUDA OLAHRAGA DAN PARIWISATA - Mansursah, Rochmat; Tjaturrini, Dyah; Kuntarto, Kuntarto (Jurnal Vokasia, 2021)
This article is entitled "Application for Ayo Wisata to Cilacap in Mandarin at the Department of Youth, Sports and Tourism of Cilacap Regency". This application is only available in Indonesian. This causes foreign tourists to find the problem of not being able to convey information clearly. Cilacap is one of the areas visited by many Chinese people both for work and for tourism. One of them is because they work at PLTU Cilacap. To fill their spare time or vacation when they are not working, they usually go to visit tourist destinations in Cilacap. The visit of Chinese tourists to Cilacap tourist destinations decreased during the Covid 19 pandemic. Therefore, in order to continue to provide tourism services as an effort to promote tourist destinations in Cilacap, the Let's Travel To Cilacap application was made in the Chinese version. This of course helps a lot of Chinese tourists, whether in Indonesia or in China, can still get this information easily. This video is made visually using the method of voiceover and subtitles. This, in addition to improving tourism services in Cilacap, also makes it easier for Chinese tourists to visually identify tourist attractions in Cilacap